"There's no place like home": Examining the associations between state eviction defense protections and indicators of biopsychosocial stress among survivors of intimate partner violence. (June 2021) - Willie, Tiara C.; Linton, Sabriya L.; Whittaker, Shannon; Martinez, Isabel; Sharpless, Laurel; Kershaw, Trace
Abstract: Housing instability is prevalent among intimate partner violence (IPV) survivors and a source of biopsychosocial stress among this population. Eviction policies play an important role in determining housing instability of IPV survivors. However, few studies have investigated whether state-level policies that prevent evictions lessen vulnerability to biopsychosocial stress among IPV survivors. This study examined the relationship between state eviction defense policy and indicators of biopsychosocial stress among 6577 IPV survivors. State-level data on IPV-related housing policies were from a compendium on homelessness and violence. Individual-level data were collected from the National Intimate Partner and Sexual Violence Survey (NISVS), a nationally representative study of noninstitutionalized U.S. women and men from Wave 1 (2010). Multilevel regression models were conducted to investigate associations between the presence of an eviction defense policy and indicators of biopsychosocial stress (i.e., headaches, sleeping, safety concerns and PTSD symptoms). Stratified multilevel modeling was conducted to examine differences in the policy-stress associations across racial and ethnic groups and gender. Nearly 26% of states had an eviction defense policy for IPV survivors. Overall, residing in a state with an eviction defense policy (vs. none) was associated with no reports of frequent headaches (B [95% CI] = −0.21 [-0.41, −0.01], p  < .05). For non-Hispanic Black survivors, residing in a state with an eviction defense policy (vs. none) was associated with reduced likelihood of reporting safety concerns (B [95% CI] = −1.36 [-2.16, −0.56], p  < .001) and PTSD symptoms (B [SE] = −1.91 [-2.82, −1.01], p  < .000). Among men survivors, residing in a state with an eviction defense policy was associated with reduced likelihood of reporting safety concerns (B [95% CI] = −0.63 [-1.26, −0.01], p  < .05). State housing policies are important protective policies for IPV survivors. For IPV survivors, the eviction defense policy may interrupt the psychological sequeale of IPV and housing instability. Highlights: Housing instability increases stress among survivors of intimate partner violence. Unfair institutional actions elevate evictions among Black and Hispanic survivors. State-level eviction defense policies may reduce housing instability and stress. Eviction defense policies were associated with reduced stress among Black survivors. A health equity approach is needed to ensure equitable access to eviction defenses.